The Use of Thermal Imaging in Free Perforator Flap Planning - Čepas, Adas; Fomkinas, Mantas; Gindriūnas, Simas; Budreckis, Kasparas; Pilipaitytė, Loreta; Rainys, Domantas (Lietuvos chirurgija, 2022)
Background. Preoperative planning and design of microsurgical perforator flaps are the main steps for successful operation. The aim of this study was to determine the concordance between thermographic images obtained with smartphone thermal imaging camera and hand-held Doppler in the anterolateral thigh flap (ALT) model. Methods. A concordance study of diagnostic tests was carried out in Hospital of Lithuanian University of Health Sciences Kaunas Clinics, Plastic and Reconstructive Surgery Department during 2020–2022. Patients’ who were scheduled to undergo reconstruction with ALT flap and healthy volunteers were included in the study. Dynamic thermal images were performed with smartphone thermal camera FLIR One PRO in the typical ALT flap territory. The number and distance of hotspots in the thermogram with respect to anterior superior iliac spine were recorded in the study protocol. Later, the examination was repeated with hand-held Doppler and the control of hotspot was performed. Sensitivity, specificity and concordance index calculations were performed. Statistical analysis was performed using IMB SPSS 23.0. Results. A total of 100 ALT flap territories were examined. 266 hotspots were detected with thermal imaging and 275 perforators with hand-held Doppler. In 96.6% of cases, hotspots detected by a thermal camera were confirmed by hand-held Doppler as perforators. The sensitivity and specificity of thermography for the detection of perforators with respect to the hand-held Doppler were 93.5% and 96.9% respectively. The measure of concordance kappa index was 0.095 (p = 0.001). Conclusion. Smartphone thermal imaging have a high concordance with hand-held Doppler in perforator mapping, thus could be considered a useful adjunct to conventional methods.